MULTILEVEL IT INNOVATIONS IN PHYSICAL EDUCATION: TRANSFORMING UNIVERSITY CURRICULUM AND PRACTICE - Lin, Zhang Hui; Jun, Chen Xiao (Research Journal of Education and Allied Studies, 2024)
Multilevel teaching, a dynamic pedagogical approach distinct from traditional methods, redefines and enhances the educational process by incorporating diverse content, organizational structures, and teaching techniques, all aligned with curriculum requirements. Traditional physical education programs at universities often follow fixed curricula and procedural norms, fostering an incremental and uninspiring learning environment. The rigidity of this approach dampens students' enthusiasm for physical activities, compromising the overall teaching quality. To address these challenges, the integration of information technology into university physical education classes emerges as a promising solution. This article explores the development of multilevel teaching models for university-level physical education, enhanced by information technology. By capitalizing on the benefits of information technology, this research not only revitalizes physical education instruction but also fuels students' engagement and holistic well-being, ultimately enhancing the quality of physical education in higher education